Soft chromophore featured liquid porphyrins and their utilization toward liquid electret applications - Avijit Ghosh (Nature Portfolio, 2019)
Though electret materials are attractive for realizing flexible mechanoelectrical devices, these materials are typically solid films. Here, the authors report stretchable ‘liquid-electret’ devices consisting solvent-free liquid porphyrins that show piezoelectric and electroacoustic functionality.